2008
DOI: 10.1007/s11745-008-3166-5
|View full text |Cite
|
Sign up to set email alerts
|

From Aquatic to Terrestrial Food Webs: Decrease of the Docosahexaenoic Acid/Linoleic Acid Ratio

Abstract: Fatty acid composition of the adipose tissue of six carnivorous mammalian species (European otter Lutra lutra, American mink Mustela vison, European Mink Mustela lutreola, European polecat Mustela putorius, stone marten Martes foina and European wild cat Felis silvestris) was studied. These species forage to differing degrees in aquatic and terrestrial food webs. Fatty acid analysis revealed significant differences in polyunsaturated fatty acid composition between species. More specifically, our results underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 37 publications
7
47
0
Order By: Relevance
“…Thus, our feeding trial suggests a reduction of all UFA, in particular of the n-3 fraction, when HIM is incorporated into fish diets in considerable proportions. This may point to a negative sideeffect of HIM, as the high supply of n-3 FA from marine animals is an important issue in the nutritional importance of fish (Astorg et al, 2004;Koussoroplis et al, 2008) The estimated intraperitoneal fat content as well as HSI and VSI were not influenced by the different dietary fatty acid profiles. Lock et al (2015) argue on the contrary that in Atlantic salmon HSI and VSI were higher in HIM fed fish because of increased hepatic and intraperitoneal fat content which they relate to the comparatively high content of C12:0 in HIMs and the better utilisation of this short chain FA compared to others.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our feeding trial suggests a reduction of all UFA, in particular of the n-3 fraction, when HIM is incorporated into fish diets in considerable proportions. This may point to a negative sideeffect of HIM, as the high supply of n-3 FA from marine animals is an important issue in the nutritional importance of fish (Astorg et al, 2004;Koussoroplis et al, 2008) The estimated intraperitoneal fat content as well as HSI and VSI were not influenced by the different dietary fatty acid profiles. Lock et al (2015) argue on the contrary that in Atlantic salmon HSI and VSI were higher in HIM fed fish because of increased hepatic and intraperitoneal fat content which they relate to the comparatively high content of C12:0 in HIMs and the better utilisation of this short chain FA compared to others.…”
Section: Discussionmentioning
confidence: 99%
“…Guler et al (2008) reported that the n-6/n-3 ratio of carp muscle was 2.0 in autumn, it was higher than in other seasons. In temperate zone, terrestrial organic matters containing a great abundance of n-6PUFAs were released into the freshwater and became the important elements of freshwater food webs (Koussoroplis et al 2008). …”
Section: Effects Of Diet Lipids On the Fatty Acid Content In Various mentioning
confidence: 99%
“…Terrestrial organisms have a greater abundance of n-6 PUFA, e.g., linoleic acid (18:2n-6). Thus, the ratio of n-3 to n-6 PUFA can be a useful indicator of the amount of aquatic versus terrestrial food in an organism's diet (Skjervold 1992;Addis 2005;Koussoroplis et al 2008).…”
Section: Introductionmentioning
confidence: 99%